Why are we not winning? An exploration of causes for continued disengagement among graduates of low-income community leadership development programs. Issue 1 (1st January 2018) - Majee, Wilson; Reed Adams, Johanna; Goodman, Laurel; Sethi, Tarunjot Kaur; Anakwe, Adaobi
Abstract: This mixed method study examines the causes of continued disengagement among graduates of a low-income community leadership development (CLD) program. Interviews were conducted with 55 CLD program graduates, 19 program facilitators, and 12 community members. Surveys were completed by 80 program graduates including the 55 who participated in interviews. Three main themes emerged with regard to community engagement: self-motivation, program leadership, and community readiness. Participants had mixed feelings on each of the themes. Overall our findings suggest that there are personal (self-motivation), programmatic (leadership and structure), and community (readiness) factors influencing the motivation to participate in CLD and transition to skills application in the community. This implies a need for CLD programs to focus on developing a holistic, inclusive, and collaborative process where low-income residents can partner with community leaders in identifying the creative solutions necessary to solve very distinct local problems.